To screen or not to screen for obstructive sleep apnea, that is the question - Turnbull, C; Stradling, J (Elsevier, 2017)
Screening tests are widely used, either in low disease prevalence populations, e.g., breast cancer screening, or more focused screening in patients declaring symptoms suggestive of a disease, such as CT coronary angiography for patients with chest pain. Three papers in this journal look at screening for obstructive sleep apnea (OSA) using questionnaires in varied populations with very different prevalences of OSA [1]; [2] ; [3]. However, there is surprisingly little evidence that such activities are valuable, or that they should divert resources away from patients with symptomatic OSA.